Literature and philosophy in Nineteenth Century British culture.
1 online resource (533 pages)
Keywords: This is the first volume in a three-volume collection of primary sources which examines philosophy and literature in nineteenth-century Britain. Accompanied by extensive editorial commentary, this collection will be of great interest to students and scholars of British Literature and Philosophy.